Islamic Perspective of Educational Communication at Al Qodiri in Forming the Characteristics of Santri - Nafilah, Zulfa Kamilatun; Mujib, Ihwan Huda Al (Journal of Language, Communication, and Tourism, 2024)
One of important aspects of education is related to how this contributes to positive changes on individuals. To do so, communication is always an important part of education especially in shaping students’ characters. This also applies at Islamic boarding schools, widely known as pondok pesantren, in Indonesia. Regarding this matter, kitab kuning which literally translates into the yellow books have been the basis of how to educate santri, students of Islamic boarding schools, to become future individuals with great characters. One of the yellow books learnt at Islamic boarding schools is Ta'lim Mutaallim. This book is one of the obligatory books learnt at Al Qadiri Islamic boarding schools in Jember. This research is a descriptive qualitative research conducted at the Al Qodiri Islamic boarding school in Jember. The results of the study show that there are 7 characters of Islamic perspective of educational communication according to Al Jarnuzi which are conveyed and taught at the Al Qodiri Islamic boarding school in shaping the characteristics of students. Those characters include: 1) the intention to learn, 2) choosing teachers, knowledge, and friends, 3) glorifying knowledge and experts in knowledge, 4) sincerity in seeking knowledge, istiqomah, and noble ideals, 5) trust, 6) wara’, and 7) learning methods